Research and prospect of intelligent internet of vehicles based on 5G technology - Rongyue YANG; Pengzhou ZHANG; Qing SONG (Dianxin kexue)
With the rapid development of 5G communication technology,in the future,V2X will take 5G communication technology as the starting point,integrate 5G vehicle unit,5G base station,5G mobile terminal,5G cloud server and other advanced equipment,to provide comprehensive and high-quality services for multi-type users.Firstly,the key technologies of V2X and its evolution to 5G era were outlined.5G is deeply integrated with the internet of vehicles,which has the technical advantages of relatively low deployment cost and clear evolution route.Then,the application and research status of 5G emerging key technologies such as mobile edge computing (MEC) and network slicing in typical application scenarios of the Internet of vehicles was focused on.Finally,the problems of 5G internet of vehicles in communication interference,network security and privacy protection,communication interference were put forward,and the research direction was pointed out.